2011
DOI: 10.1371/journal.pone.0021988
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Gastric Carcinogenesis in Cebus apella Nonhuman Primates

Abstract: The evolution of gastric carcinogenesis remains largely unknown. We established two gastric carcinogenesis models in New-World nonhuman primates. In the first model, ACP03 gastric cancer cell line was inoculated in 18 animals. In the second model, we treated 6 animals with N-methyl-nitrosourea (MNU). Animals with gastric cancer were also treated with Canova immunomodulator. Clinical, hematologic, and biochemical, including C-reactive protein, folic acid, and homocysteine, analyses were performed in this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
3
16
0
Order By: Relevance
“…The detection of MYC immunoreactivity in intestinal metaplasia of individuals from three Northern Brazil populations corroborates previous studies of our group that demonstrated the presence of MYC protein overexpression only in intestinal metaplasia and neoplastic tissue from all patients with intestinal type gastric cancer, which is preceded by preneoplastic lesions [21-23], as well as in intestinal metaplasia of non-human primates treated with N-methyl-nitrosourea (MNU) [24]. On the other hand, MYC immunoreactivity was described in gastritis samples, as well as intestinal metaplasia, in Asian populations [15,25-27].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The detection of MYC immunoreactivity in intestinal metaplasia of individuals from three Northern Brazil populations corroborates previous studies of our group that demonstrated the presence of MYC protein overexpression only in intestinal metaplasia and neoplastic tissue from all patients with intestinal type gastric cancer, which is preceded by preneoplastic lesions [21-23], as well as in intestinal metaplasia of non-human primates treated with N-methyl-nitrosourea (MNU) [24]. On the other hand, MYC immunoreactivity was described in gastritis samples, as well as intestinal metaplasia, in Asian populations [15,25-27].…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, this is the first study to sensitively quantify MYC mRNA expression in precancerous gastric lesions. The increased MYC expression in intestinal metaplasia supports a previous study of our group in non-human primates, in which we demonstrated a continuous increase of MYC mRNA expression during the sequential steps of gastric carcinogenesis in MNU-treated animals [24]. In these animals, the mRNA expression increased about 3-fold in intestinal metaplasia compared to normal gastric mucosa.…”
Section: Discussionsupporting
confidence: 89%
“…Universal peroxidase-conjugated secondary antibody kit (DakoCytomation, USA) was used for the detection system and 3,30-diamino-benzidine/H 2 O 2 (Dakocytomation, Denmark) was used as the chromogen. Positive ER, PR or MYC expression was defined as clear nuclear immunostaining in more than 10% of tumor cells [18], [19], [20], [21]. HER2 protein staining was scored as 0 (negative), 1+(weakly positive), 2+ (moderately positive) and 3+ (strongly positive) [2].…”
Section: Methodsmentioning
confidence: 99%
“…Experiments in vivo and in vitro point out that treatment with CA can cause tumor size reduction and regression in animals, and can also recover cells viability after they were damaged [2] . NMU was successfully used as an inductor of gastric carcinogenesis in Cebus apella and the treatment with CA was able to restore several hematologic measurements in those animals, suggesting that CA can be used during/after chemotherapy to increase the tolerability and duration of anticancer treatments [3] . Thus, the aim of the present study was to evaluate possible protective effects mediated by CA against the genotoxicity caused by oral MNU ingestion in non-human primates of the specie Cebus apella.…”
Section: Introductionmentioning
confidence: 99%